PENGGUNAAN MEDIA KOMIK BERBAHASA INGGRIS SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN BAHASA INGGRIS PADA SISWA KELAS VIII SMPN 3 TELUK KUANTAN - Sasti Karmiani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study aims to improve the ability to read English comprehension of class VIII A students at SMPN 3 Teluk Kuantanthrough English-language comic media. This research is a classroom action research conducted by following John Elliot'smodel research procedure which includes planning, action, observation, reflection or evaluation. The study was conducted atSMPN 3 Teluk Kuantan in 2018-2019 academic year in odd semester for students of class VIII A, totaling 21 students. Theresults showed that before being given learning using English-language comic media, the average score of students' readingcomprehension was 57.38 (28.57 %) with less criteria. After reading comprehension learning using English language comicmedia the first cycle the average score of students' reading comprehension ability increased to 64.76 (57.14 %) whichincluded in the criteria sufficient, and learning is done in the second cycle students' reading comprehension ability has anincrease in the average value and a percentage of 75.23 (80.95 %) with good criteria.